Pengaruh Mobile banking Terhadap Fee Based Income - Ahim Surachim; Yusuf Murtadlo Hidayat; Nabila Haura Zain (Strategic : Jurnal Pendidikan Manajemen Bisnis, 2021)
The Covid-19 pandemic has reduced bank profits. Fee based income can be an alternative in obtaining income during pandemic. Mobile banking is one off the services that bank provide to earn income through fee based income. This study was conducted to determine the effect of mobile banking on fee based income. This research use dectiptive verification metod. Use secondary data for the 2016-2020 period with purposive sampling, 5 companies were obtained as sample. Veriveication testing is using panel data regression test. The result showed that mobile banking had a positive effect on fee based income.